The Effect of Numeracy Literacy-Based Learning Management and Digital Media Utilization on Students' Perceived Mathematics Learning Outcomes in Public Junior High Schools - Julisa Riviny Sambur; Mozes M. Wullur; Deitje A. Katuuk; Romi J. Mongdong (JR Education, 2026)
Mathematics education in Indonesia continues to face challenges, as evidenced by low national rankings in PISA 2022 and ANBK assessments, reflecting persistent gaps in numeracy competency and contextual problem-solving skills among students. This study aimed to examine the effect of numeracy literacy-based learning management and digital media utilization, both partially and simultaneously, on students' perceived mathematics learning outcomes. A quantitative explanatory approach with a correlational design was employed. Data were collected from 163 eighth-grade students selected through proportional random sampling from a population of 275 students across two public junior high schools in Paal Dua District, Manado City, using validated Likert-scale questionnaires analyzed through multiple linear regression. Numeracy literacy-based learning management exerted a positive and significant effect on perceived learning outcomes (β = 0.548, t = 9.512, p < 0.001), and digital media utilization also had a positive and significant effect (β = 0.333, t = 5.769, p < 0.001). Simultaneously, both independent variables significantly explained 57.2% of the variance in students' perceived mathematics learning outcomes (F = 106.820, p < 0.001). Numeracy literacy-based learning management was identified as the more dominant predictor. Integrating numeracy literacy-oriented learning management with effective digital media utilization constitutes a relevant and essential strategy for improving the quality of mathematics learning in 21st-century education. Educational practitioners and policymakers should prioritize teacher professional development that emphasizes both numeracy literacy integration and purposeful digital media use to enhance student mathematics achievement.